Sol–Gel Synthesis and Photocatalytic Activity of Graphene Oxide/ZnFe2O4-Based Composite Photocatalysts - Tong, Beibei; Shi, Longfei; Liu, Xiaohong (Frontiers in Materials, 2022)
ZnO (ZO), Fe2O3 (FO), and graphene oxide (GO)/ZO/FO/ZnFe2O4 (ZFO) composite photocatalysts have been synthesized successfully via a simple sol–gel method and low-temperature technology. The phase structure and microstructural analysis confirmed that the GO/ZO/FO/ZFO magnetic separation photocatalyst is composed of GO, hexagonal ZnO, rhombohedral Fe2O3, and spinel ZnFe2O4 without any other impurities. The GO/ZO/FO/ZFO composite photocatalysts have a high visible light optical absorption coefficient and photocatalytic activity for degrading dyes, refractory pollutants, and antibiotics. The degradation percentages of methyl orange, tetrabromobisphenol A, and oxytetracycline hydrochloride by the GO/ZO/FO/ZFO magnetic separation photocatalyst were 98% for 180 min, 99% for 150 min, and 85% for 180 min, respectively. The special synthesis path leads to the formation of a special heterojunction between GO, ZnO, Fe2O3, and ZnFe2O4, which does not change the optical band gap value of the main lattice Fe2O3, and enhances the surface defects of the GO/ZO/FO/ZFO magnetic separation photocatalyst, resulting in high charge carrier transfer and separation efficiency of the catalyst and then enhanced the photocatalytic activity of the GO/ZO/FO/ZFO magnetic separation photocatalyst.